Analisis Sistem Informasi Akuntansi Perlengkapan Barang melalui SISTERPAULA pada Puskesmas Kecamatan Pulogadung - Ni Made Divani Safitri; Hera Khairunnisa; Ayatulloh Michael Musyaffi (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
The management of general inventory at Puskesmas Kecamatan Pulogadung, which involves various service units and subsidiary health centers, has been properly recorded; however, it still faces challenges due to the manual recording process during the monthly usage recapitulation stage. These conditions result in delays in data recapitulation, potential recording errors, and difficulties in preparing inventory reports. This study aims to design an updated inventory recording system that automates integrated inventory data recapitulation. The research method used is Research and Development, focusing on system design and the development of a user guide module. The proposed system includes recording incoming and outgoing goods and generating inventory reports directly connected to Microsoft Excel. The results of this study are an inventory recording system design and a user guide module expected to improve the effectiveness, accuracy, and accountability of inventory management at Puskesmas Kecamatan Pulogadung